An Implementation of Fuzzy Logic to Salinity Control of Chanos chanos Pond Based on Internet of Things - Indra, Jamaludin; Fauzi, Ahmad; Murnawan (International Journal of Psychosocial Rehabilitation, 2020)
Chanos chanos has great potential to become a business field in Indonesia. To manage a farm many factors must be considered, one of the factors that must be managed well is Water Salinity. At present in Tanjungpakis - Karawang Village, pond farmers still use traditional methods to find out the condition of pond water. Farmers do it by looking at the color of water, the smell of water and using taste buds. Generally brackish chanos chanos can grow well in water conditions that have saline levels ranging from 5 - 25 ppt. With changing environmental conditions and weather, the salinity of ponds usually increases or decreases, during the dry season the pond water salinity usually increases quite dramatically, whereas in the rainy season the pond’s water salinity is usually at normal or even less normal limits. Farmers in the pond do additional fresh water in the dry season and increase sea water in the rainy season so that the pond’s water salinity remains stable. this study made a water salinity control system for chanos chanos fishponds. The control system is carried out by measuring the salinity of pond water using conductivity sensors, processing data using fuzzy logic, direct monitoring through computers and mobile phones and using aquaculture, namely freshwater and sea water pumps to maintain the stability of salt levels in the ponds. This system runs well with an accuracy rate of 87.8% compared to refractor meter and condition determination using fuzzy logic with 100% accuracy.